Localised low velocity impact performance of short glass fibre reinforced polyamide 66 oil pans - Mouti, Zakaria (Cranfield University, 2012)
This thesis focuses on the mechanical properties of short glass fibre reinforced polyamide 66 material used in automotive composite structures, and its impact resistance under localised low velocity impact. The main application of this research concerns the impact performance of an oil pan component susceptible to stone impact damage. The thesis reviews the current state-of-the-art of thermoplastic polyamide materials with an overview of the glass fibre reinforced polyamide under-the-hood components, as well as its manufacturing and processing techniques. The study explores much of the work published in the literature so as to identify the fundamental parameters determining the impact resistance. It then concentrates on assessing the mechanical properties of the material subjected to quasi-static loads and impacts considering the influence and consequences of atmospheric or weathering conditions such as the moisture and salt uptake and the variation of temperature. The experimental work employed a universal testing machine for the quasi-static tests, drop weight tower and projectile air gun to carry out the dynamic tests. The testing involves different polyamide grades and impact modifier material in small specimens and full-scale oil pan components so as to gain important insights into the material-geometrical coupling effects. In correlation with the experiments, a finite element analysis was conducted to predict capability and simulate impact events using LS-DYNA solver. The simulation allowed putting to the test and comparing different protective design features. The post-testing investigations focused on the damage assessment and failures at micro- and macro-scales on the structure using visual inspection, scanning electron microscopy and ultrasound flaw detector. This was intended to bring detailed understanding of the failure mechanisms and also shed some light into damage tolerance of typical under-the-hood thermoplastic polyamide components. Investigation results indicated that impact resistance properties of short glass fibre reinforced polyamide 66 grades are sensitive and influenced by moisture and salt uptakes, temperature ageing and air oxidation. In general, the increase of these parameters reduces the material strength but at the same time improves its strain. The study also compares different structures and shows the significant contribution of the design in terms of shock absorption and stress distribution. The proposed oil pan design with protective ribbing pattern combined with a superior material with rubbery phase considerably improves the impact resistance of the full-scale automotive component studied.